Tolerability and Long-term Outcomes of Dose-Painted Neoadjuvant Chemoradiation to Regions of Vessel Involvement in Borderline or Locally Advanced Pancreatic Cancer. (July 2018) - Wo, Jennifer Y.; Niemierko, Andrzej; Ryan, David P.; Blaszkowsky, Lawrence S.; Clark, Jeffrey W.; Kwak, Eunice L.; Lillemoe, Keith D.; Drapek, Lorraine N.; Zhu, Andrew X.; Allen, Jill N.; Faris, Jason E.; Murphy, Janet E.; et al.
Abstract : Purpose: We reviewed our experience involving patients with borderline resectable or locally advanced pancreatic cancer, treated with the dose-painted (DP) boost technique to regions of vessel involvement which preclude upfront surgical resection. We evaluated patient outcomes with respect to tolerability and treatment outcomes. Materials and Methods: We retrospectively reviewed 99 patients with borderline resectable (n=25) or locally advanced pancreatic cancer (n=74) treated with DP-neoadjuvant chemoradiation from 2010 to 2015. Tumor and regional lymph nodes were prescribed 50.4 Gy and the region around the involved blood vessel was boosted to 58.8 Gy in 28 fractions. The primary outcome was acute toxicity and late duodenal toxicity. Secondary outcomes included conversion to surgical resectability, local failure, disease-free survival, and overall survival (OS). Cox proportional hazards models were performed to evaluate for predictors of survival. Results: All but 1 patient completed chemoradiation. The rates of grade 2+ and 3+ nausea were 40% and 12%, respectively. With regards to late toxicity, 5 patients developed potential RT-related grade 3+ duodenal complications including duodenal ulceration/bleeding (n=3) and duodenal stricture (n=2). With a median follow-up of 15 months, the median OS was 18.1 months. Among 99 patients in our study, 37 patients underwent surgical resection. For patients who underwent surgical resection (n=37), the median OS was 30.9 months. On multivariate analysis, only normalization of CA 19-9 post-RT was associated with improved OS. Conclusions: We found that DP-neoadjuvant chemoradiation to regions of vessel involvement is both feasible and well tolerated. In addition, we demonstrated that over one third of patients with initially deemed unresectable disease were able to undergo surgical resection after receiving neoadjuvant therapy including DP-chemoradiation. Abstract : Supplemental Digital Content is available in the text.